Don't Blame the Blacks - pamphlet against racial discrimination (1958)
1958 1945-1960 "Don't Blame the Blacks - pamphlet against racial discrimination" [T0363.jpg], 1958 This pamphlet, written by the Afro-West Indian Union with a foreword by the secretary of the Nottingham and district Trades Council condemns racial discrimination and racism against immigrant workers, and explains some of the reason for immigration to Britain, particularly from Jamaica.